2015
DOI: 10.1093/jat/bkv099
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Synthetic Cathinones: Implications for Forensic Toxicology

Abstract: The synthetic cathinones represent an important class of designer drugs. The widespread attention and publicity associated with these psychostimulants have resulted in numerous legislative actions at state and federal levels throughout the USA. These amphetamine-like compounds are characterized by a β-keto functional group. Although the synthetic cathinones share many properties of their phenethylamine counterparts, the presence of the ketone moiety is responsible for a number of unique and distinct difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…The data reported in Figure a indicated that the analytes were quite stable at the temperature tested, except for some cathinones, particularly 2‐FMC and 2‐methoxymethcathinone that gave lower recoveries particularly at 150 °C. The thermolability of cathinones has been previously reported in GC experiments and was reported to be related to the oxidative decomposition of these compounds, resulting in an enamine or imine formation . Interestingly, Archer et al studied the stability of fluoromethcathinone isomers and observed a decrease in stability for the series 4‐fluoro, 3‐fluoro and 2‐fluoromethcathinone, demonstrating that the position of the fluorine atom was of paramount importance .…”
Section: Resultsmentioning
confidence: 91%
“…The data reported in Figure a indicated that the analytes were quite stable at the temperature tested, except for some cathinones, particularly 2‐FMC and 2‐methoxymethcathinone that gave lower recoveries particularly at 150 °C. The thermolability of cathinones has been previously reported in GC experiments and was reported to be related to the oxidative decomposition of these compounds, resulting in an enamine or imine formation . Interestingly, Archer et al studied the stability of fluoromethcathinone isomers and observed a decrease in stability for the series 4‐fluoro, 3‐fluoro and 2‐fluoromethcathinone, demonstrating that the position of the fluorine atom was of paramount importance .…”
Section: Resultsmentioning
confidence: 91%
“…Psychostimulants of the designer cathinone class (i.e., beta-ketone amphetamines) are known colloquially as “bath salts” [Karch et al, 2015; Kerrigan et al, 2016]. Mechanistically, synthetic cathinones have been classified according to two distinct actions on the monoamine system.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some tricks to reduce this problem, LC‐MS is a valuable alternative and is frequently used for the analysis of NPS. One example could be quantification, from only 100 µL human urine samples, of 40 NPS and their metabolites by LC‐ESI‐MS with a solid phase extraction . Other examples are evaluation of the patterns of drug abuse from London nightclubs confirming intake of psychoactive drugs within studied group or analysis of synthetic cathinones in the seized products utilizing triple quadrupole analyser .…”
Section: Introductionmentioning
confidence: 99%
“…One example could be quantification, from only 100 µL human urine samples, of 40 NPS and their metabolites by LC-ESI-MS with a solid phase extraction. 7 Other examples are evaluation of the patterns of drug abuse from London nightclubs confirming intake of psychoactive drugs within studied group 8 or analysis of synthetic cathinones in the seized products utilizing triple quadrupole analyser. 9 Apart from GC-MS and LC-MS, also capillary electrophoresis (CE) is sometimes used to confirm the presence of psychoactive substances.…”
Section: Introductionmentioning
confidence: 99%